A igreja evangélica no processo histórico da educação infantil no município de Parintins-Am: contribuições do Centro Educacional Infantil Novo Israel - Rodrigues, Edinelson Auzier (Brasil, 2022)
The research work of qualitative approach presents questions pertinent to the contribution of the evangelical church in the historical process of early childhood education. The research aimed to investigate the contribution of the Evangelical Church in the Historical Process of Early Childhood Education in the municipality of Parintins-AM. In this sense, the historical-dialectical method was used for the research, aiming to know, through the history of a Children's Educational Center, the contribution of the Evangelical Church in the historical process in Early Childhood Education in Parintins-AM. As a methodological procedure, bibliographic research and field research were used to produce the research data, the application of questionnaires for educators and analysis of the history of the said center with records in the field notebook was performed. The research is based on: Aranha (2006), Ariès (1973), Basto (2012), Butel (2018), Figueiredo; Amoedo; Gomes (2017), Gil (2008), Kramer (2006), Kuhlmann Jr. (1998), Lakatos (2003), Oliveira (2011, 2013), Rousseau (1762), Santos (2007), Soares (2013, 2017) e Vieira (2015). The research data reveal the social function of the Evangelical Church in the historical-social construction of Early Childhood Education in the municipality of Parintins - AM, as well as highlight the contribution of the New Israel CIS in early childhood education, with an educational proposal that contemplates religious principles in the education of children, while respecting the laicity and multiculturalism of parintinense families, considering the social role of Early Childhood Education as a promoter of the integral development of children and the formation of values in dialogue with families. It is expected that this research contributes to the studies on the theme addressed, since knowing the trajectory of Early Childhood Education in this municipality